2021
DOI: 10.1017/s0033291721002695
|View full text |Cite
|
Sign up to set email alerts
|

Associations between mental wellbeing and fMRI neural bases underlying responses to positive emotion in a twin sample

Abstract: Background Although mental wellbeing has been linked with positive health outcomes, including longevity and improved emotional and cognitive functioning, studies examining the underlying neural mechanisms of both subjective and psychological wellbeing have been sparse. We assessed whether both forms of wellbeing are associated with neural activity engaged during positive and negative emotion processing and the extent to which this association is driven by genetics or environment. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…This form of preferential association between happiness and potentiated response to positive events over negative ones is further supported by neuroimaging evidence from fMRI research, which reported increased amygdala reactivity to positive but not negative stimuli as a function of trait happiness ( Cunningham and Kirkland, 2013 ). A similar pattern of association was found between self-reported well-being and inferior frontal gyrus reactivity to positive stimuli ( Park et al. , 2021 ).…”
Section: Discussionsupporting
confidence: 72%
“…This form of preferential association between happiness and potentiated response to positive events over negative ones is further supported by neuroimaging evidence from fMRI research, which reported increased amygdala reactivity to positive but not negative stimuli as a function of trait happiness ( Cunningham and Kirkland, 2013 ). A similar pattern of association was found between self-reported well-being and inferior frontal gyrus reactivity to positive stimuli ( Park et al. , 2021 ).…”
Section: Discussionsupporting
confidence: 72%
“…Finally, using multivariate twin modelling, we have been able to confirm the role of shared genetics and environmental factors in each of the phenotypic associations. For instance, we found evidence to suggest that the links between well-being and variables including EEG resting state (ABD interaction36) depression and anxiety symptoms32 and cognitive inhibition34 were mostly genetically driven, whereas the links between well-being and variables including emotion-related neural activity38 and pons volume37 were mostly environmentally driven. Together, these results identify for the first time how genetics versus life experience can modulate the links between neural markers and well-being.…”
Section: Introductionmentioning
confidence: 95%
“… 34 We also observed faster behavioural response times to happy faces in individuals with high well-being, while those with higher depression and anxiety symptoms displayed slower reaction times. 35 On a neural level, we reported associations between higher well-being and an electroencephalography (EEG) resting-state profile of high alpha and delta and low beta (ABD) power, 36 a reduced pons grey matter volume localised to the locus coeruleus, 37 increased fMRI activity in the right inferior frontal gyrus in response to happy faces during an emotional faces task, 38 and decreased insula activation during a sustained attention continuous performance task. 39 Finally, in terms of genetics, we confirmed a polygenic score of well-being to be predictive of COMPAS-W scores, and derived nine subthreshold candidate genes from a genome-wide association study analysis of the COMPAS-W scores.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…These cognitive functions have also been associated with mental wellbeing when assessed using performance measures like reaction time and accuracy 65 , 66 . The ability to quickly process and recognize emotional stimuli, especially happy facial expressions, has been associated with higher wellbeing using emotion processing tasks evaluated at the behavioural and neural fMRI level 67 , 68 . Better facial processing is linked to higher empathy 69 , and may facilitate supportive social interactions which bolster support resources and subsequently wellbeing.…”
Section: Introductionmentioning
confidence: 99%